The relationship between dietary inflammatory index (DII) and early renal injury in population with/without hypertension: analysis of the National health and nutrition examination survey 2001–2002 - Jingda Huang; Huimin Li; Xu Yang; Chuyue Qian; Yihui Wei; Mindan Sun (Renal Failure)
Background Inflammation plays a crucial role in occurrence of kidney injury, and specific dietary patterns can influence systemic inflammation levels. However, the relationship between dietary inflammatory potential and early-stage kidney damage remains unclear.Method 2,108 participants was recruited from 2001–2002 National Health and Nutrition Examination Survey (NHANES). Dietary Inflammatory Index (DII) is utilized to assess dietary inflammatory potential, calculated through a 24-h dietary recall questionnaire. Early renal injury was evaluated using urinary albumin to creatinine (UACR), cystatin C (CysC), β-2 microglobulin (β2M), and estimated glomerular filtration rate (eGFR) based on serum creatinine (eGFRs), cystatin C (eGFRc), and both Scr and CysC (eGFRs&c). Participant characteristics were analyzed, and association between DII, hypertension, and early renal injury markers was explored using multiple linear and logistic regression models.Results The average age of participants was 53.9 years. DII exhibited a positive correlation with UACR (β = −0.048[0.017,0.078]), β2M (β = 0.019[0.010,0.027]), CysC (β = 0.012 [0.004,0.021]). Conversely, a negative correlation was observed between DII and eGFRc (β = −1.126[−1.554, −0.699]), eGFRs&c (β=-1.101[−1.653, −0.549]). A significant association was observed between hypertension and abnormality of early kidney damage markers. Subgroup analysis reveals that the positive correlation between DII and the occurrence of abnormal markers of early kidney damage is only observed in individuals with hypertension. Furthermore, an interaction between DII and hypertension was detected in eGFRs&c (OR:1.250[1.042, 1.499], p for interaction = 0.03).Conclusion Higher levels of DII may be associated with occurrence of early kidney damage. For individuals with hypertension, avoiding excessive consumption of pro-inflammatory foods may reduce the risk of renal injury.